HAK ATAS PENDIDIKAN DALAM SISTEM PENERIMAAN PESERTA DIDIK BARU BERBASIS ZONASI DI INDONESIA - I Putu Andika Pratama; Ketut Suardita (Jurnal Komunikasi Hukum, 2023)
Education is the human’s right as the main fondation in the development of the nations. The school zoning system is implemented in the process of accepting new student in order to acess the education evenly. The problem of this research are related to the rules of accepting new students through the zoning system and the authority in determining their zones. This research is aimed to be a critic related to school zoning process which is still becoming an issue nowdays. This research was normative analyzed by using three methods such as statue approach, fact approach and analytical conceptual aproach. The results in this research showed that there is vagueness norm in determining the school zone which has caused some problems for the new students. Therefore, the government’s authority is needed to interpretation this vagueness, and give freedom in determining the zoning area for new student who cannot enter the school because of the long distance. It should be done in order to implement the educational justice and enforcement of human rights in Indonesia.